Gastroenteritis Outbreak of Rotavirus G3P[8] in a Secondary School in Pathum Thani Province, Thailand, 2022 - Thanasitthichai, Siriyakorn; Suphanchaimat, Rapeepong; Sawangpol, Chanasan; Wongsuwanphon, Saruttaya; Duanyai, Chanakan; Boonwisat, Peewara; Soudprakhon, Chettha; Rattanathamsakul, Thanit (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2023)
On 14 Sep 2022, the Division of Epidemiology was notified of a cluster of food poisoning in a secondary school. We conducted an investigation to describe the epidemiological characteristics of the outbreak, identify the causative agent, source of illness, and possible risks, and provide control measures. An electronic-based questionnaire was distributed to school members. Students and staff were interviewed. Inspection of the school canteen, water supply system, toilets, and hand-washing facilities as well as observation of personal and food hygiene practices among food handlers were done. A retrospective cohort study was conducted. The overall attack rate was 40.4% (684/1,695). Most cases were students (95.9%). Thirteen out of twenty-eight rectal swabs were positive for rotavirus, with two being identified as genotype G3P[8]. Being exposed to foods or drinks from the school canteen was a significant risk factor (adjusted odds ratio (AOR) 2.35, 95% CI 1.23–4.52), and bringing a drink to school was protective (AOR 0.67, 95% CI 0.50–0.88). Although rotavirus was not detected in the environment, contamination of groundwater used for cooking and drinking was evident. We recommend routine water quality testing and installation of groundwater treatment to ensure the safety of the water supply.